The Political Economy of the Automobile Industry in ASEAN: A Cross-Country Comparison - Wan-Ping Tai (Centre for Business and Diplomatic Studies (CBDS) Bina Nusantara University, 2016)
The automobile industry plays a leading role in a country’s industrialization. Various countries have used different methods to identify a model of industrial development. For developing countries, establishing the automobile industry is crucial for promoting industrialization. After Southeast Asian countries achieved independent, their automobile industries underwent establishment and development stages. The domestic and overseas competiveness of the automobile industries in ASEAN have received global attention.How can the industrial development of Thailand, Indonesia, Malaysia, and the Philippines, which are ASEAN countries, be understood? Researchers have proposed various views regarding the industrial development of these four ASEAN countries. We researched the political economy of these countries to understand the development of their automobile industries. Thailand’s automobile industry was successfully developed because of the government’s crucial role in implementing a coordinated market economy and national system of innovation. In Indonesia, government–business relations hampered the government’s efforts to meet society and market needs, thereby limiting the country’s industrialization. Malaysia must learn how to coordinate its industries with a market economy through liberalization and coordination. The Philippines has positioned its automobile industry on manufacturing automotive parts because of the country’s limited industrialization.Theoretically, following the 1997 Asian financial crisis, these ASEAN countries have adopted market economy-oriented policies; however, because of the historical context of political economy, the development of their automobile industries has varied. Under the context of globalization, the economic systems of various countries have exhibited low convergence. In this study, we show that embedded liberalism is the preferred interpretation in ASEAN automobile industry development. In other words, researchers should look beyond convergence theory and consider the political economy characteristics of various countries. Accordingly, further comparative research must be conducted to clarify the differences in the economic systems and policies in ASEAN studies.